2017
DOI: 10.3892/ijmm.2017.3109
|View full text |Cite
|
Sign up to set email alerts
|

Particulate matter 2.5 regulates lipid synthesis and inflammatory cytokine production in human SZ95 sebocytes

Abstract: A large body of evidence indicates that particulate matter (PM)2.5 is associated with various negative effects on human health. However, the impact and molecular mechanism of PM2.5 on the skin have not been elucidated. Therefore, the present study aimed to investigate the effects of two types of PM2.5 [water-soluble extracts (W-PM2.5) and non-water-soluble extracts (NW-PM2.5)] on cell proliferation, cell cycle progression, lipid synthesis, and inflammatory cytokine production of human SZ95 sebocytes. The resul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
28
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(31 citation statements)
references
References 33 publications
1
28
0
Order By: Relevance
“…In normal human epidermal keratinocytes (NHEKs) exposed to O 3 , activation of the aryl hydrocarbon receptor (AHR) induced the expression of several cytochrome P450 genes, including CYP1A1 . AHR activation and increased CYP1A1 expression have also been reported after exposure to B[a]P, PM 2.5 and water‐soluble tobacco smoke extracts …”
Section: Biochemical Changes and Molecular Mechanisms Induced By Pollmentioning
confidence: 99%
“…In normal human epidermal keratinocytes (NHEKs) exposed to O 3 , activation of the aryl hydrocarbon receptor (AHR) induced the expression of several cytochrome P450 genes, including CYP1A1 . AHR activation and increased CYP1A1 expression have also been reported after exposure to B[a]P, PM 2.5 and water‐soluble tobacco smoke extracts …”
Section: Biochemical Changes and Molecular Mechanisms Induced By Pollmentioning
confidence: 99%
“…Ca 2+ influx and the expression of pro-inflammatory cytokines are important downstream events that are regulated by TRPV 1 [ 9 , 27 ], the expression of which is in turn upregulated by UPM treatment. In this study, the level of Ca 2+ influx and the expression levels of IL-8, TNF-α, and IL-1β were increased by UPM treatment.…”
Section: Discussionmentioning
confidence: 99%
“…A number of studies have shown that UPM affects several organs; including the cardiovascular and pulmonary systems [ 1 , 2 , 3 , 4 ], as well as several cell types including lung cells; macrophages; and epithelial cells [ 5 , 6 , 7 ]. In addition; epidemiological studies have shown that UPM exposure is correlated with several human diseases including bronchial asthma, chronic obstructive pulmonary disease, lung cancer, atherosclerosis, ischemic stroke, congestive heart failure, myocardial ischemia, and birth defects [ 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…In accordance with the histopathology of chloracne, agonistic ligation of AHR accelerates epidermal terminal differentiation and keratinization [26][27][28]. Upon AHR stimulation, the proliferation and lipid synthesis of sebocytes are impaired, probably by the switching of sebocytes toward keratinocyte-like differentiation [21,29,30]. In this review, we focus on the AHR signaling related to chloracne and highlight its potential treatment using NRF2 agonist.…”
Section: Introductionmentioning
confidence: 90%